Plexiform Neurofibroma during Pregnancy, a Case Report from College Teaching Hospital, Kohalpur - Sharma, Nirmala; B.C., Durga (Journal of Nepalgunj Medical College, 2019)
Plexiform neurofibromas are rare variant (30%) of neurofibromatosis type 1 (NF-1) in which neurofibromas arise as large deforming masses from multiple nerve endings involving also connective tissues and skin folds. We report a case of 24 years old female, second gravida and one parity with diagnosis of plexiform neurofibromatosis made in previous pregnancy with remission of symptoms after pregnancy and accentuation during second pregnancy with positive pregnancy outcome.